PELAKSANAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENTS DIVISION (STAD) DALAM MENINGKATKAN PRESTASI BELAJAR FIKIH DALAM PENDIDIKAN ISLAM - Anisiya, Dzirwah; man, Sukar; Aulia, Aina; Aziz, Abdul (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2024)
This study aims to describe: 1) Management of Fiqh learning and academic achievement in Madrasah Ibtidaiyah (MI), 2) The process of implementing Fiqh learning management with the Student Teams Achievement Division (STAD) Method in MI, 3) students' academic achievement after implementing Fiqh learning management with the STAD Method. This study uses qualitative research conducted at MI Miftahul Ulum Jogoloyo Demak, the type of action in this study is classroom action research. The results of this study are: 1) Fiqh learning management in MI in general still uses classical learning management, namely teachers are more active than students then Academic achievement in MI in general is below and fits with KKM even if it is above KKM it is only slightly higher as student learning achievement than before, 2) The process of implementing Fiqh learning management with the STAD Method in MI can be implemented with class management in the form of creating student groups then students transmit assignments. Thus, the assessment is not only assessed by the practicing teacher who is conducting the research, but is also carried out by students in groups, 4) Students' academic achievement after using the STAD Method increased higher compared to previous learning achievement.